2002
DOI: 10.1159/000070422
|View full text |Cite
|
Sign up to set email alerts
|

Bound Thrombin from Crushed Clots Is Composed of α-Thrombin and the N-Terminal Regions of α- and γ-Chains of Fibrinogen

Abstract: We aimed at clarifying the structural characteristics of the bound thrombin that is liberated by mechanical breakdown of fibrin clots. Fibrin clots were prepared with bovine thrombin and rabbit fibrinogen, and were crushed mechanically with a glass rod. The supernatant of the crushed clots was subjected to immunoaffinity chromatography to isolate the bound thrombin. Western blotting analysis revealed that the bound thrombin could be reacted with both antithrombin and antifibrinogen under unreduced conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Preparation of bound thrombin was carried out as previously described [15, 20]. In brief, a mixture of 0.5 ml of bovine α-thrombin (500 U/ml) and 2.5 ml of rabbit fibrinogen (1.5 mg/ml in serum-free DMEM) was incubated for 15 min at 37°C to allow a clot to form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of bound thrombin was carried out as previously described [15, 20]. In brief, a mixture of 0.5 ml of bovine α-thrombin (500 U/ml) and 2.5 ml of rabbit fibrinogen (1.5 mg/ml in serum-free DMEM) was incubated for 15 min at 37°C to allow a clot to form.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported some unique biological and physicochemical characteristics of bound thrombin [14,15,16], including platelet aggregation, complex with fibrin fragments. We also demonstrated that bound thrombin enhanced the phenotype conversion of VSM cells towards a synthetic type by upregulating mRNA expressions of SMemb and plasminogen activator inhibitor type 1 (PAI-1) by the comparative reverse transcription polymerase chain reaction (RT-PCR) method [17].…”
Section: Introductionmentioning
confidence: 99%